2013
DOI: 10.1149/05801.1495ecst
|View full text |Cite
|
Sign up to set email alerts
|

Improving ORR Activity of Group 4 and 5 Metal Oxide-Based Cathodes for PEFCs

Abstract: In order to develop a non-precious metal cathode for PEFCs, we have tried to improving oxygen reduction activity of Zr oxide-based cathodes. We succeeded to prepare Zr oxide-based cathodes with fine primary particles using zirconium oxy-phthalocyanine as a starting material. However, secondary particle size was very large, resulting that the activity was insufficient. Therefore, we performed ball mill to crack secondary particles for increasing the actual surface area. In addition, nitridation of oxide-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…With a maximum volumetric ORR activity of ≈0.04 A/cm 3 observed in PEMFC configuration at 80 • C, the DoE target of 300 A/cm 3 is missed by almost four orders of magnitude. 41 Although the highest gravimetric activities reported in literature are ≈10 times higher than the values found in this study, 38 they still seem far away from technical applicability, with a projected maximum volumetric current density of ≈3 A/cm 3 at 80 • C. Moreover, in the most active materials reported in the literature, the presence of iron, which is known to form ORR active Fe-N-C species when heat treated in presence of carbon and nitrogen, appears likely, questioning the activity values ascribed to (defective) ZrO 2 . Rotating ring disk electrode measurements on the most active material examined in this study revealed a main ORR reaction pathway toward hydrogen peroxide in acidic environment.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…With a maximum volumetric ORR activity of ≈0.04 A/cm 3 observed in PEMFC configuration at 80 • C, the DoE target of 300 A/cm 3 is missed by almost four orders of magnitude. 41 Although the highest gravimetric activities reported in literature are ≈10 times higher than the values found in this study, 38 they still seem far away from technical applicability, with a projected maximum volumetric current density of ≈3 A/cm 3 at 80 • C. Moreover, in the most active materials reported in the literature, the presence of iron, which is known to form ORR active Fe-N-C species when heat treated in presence of carbon and nitrogen, appears likely, questioning the activity values ascribed to (defective) ZrO 2 . Rotating ring disk electrode measurements on the most active material examined in this study revealed a main ORR reaction pathway toward hydrogen peroxide in acidic environment.…”
Section: Discussioncontrasting
confidence: 46%
“…catalysts.-At a potential of 0.8 V RHE , a practical comparison of ORR activities on ZrO 2 based catalysts in acid can be found in Table I, prepared either from the same precursor as in our case (i.e., from ZrOPc) or from ZrO(NO 3 ) 2 and supported on either XC-72 Vulcan carbon, Ketjenblack, carbon nanotubes (CNTs), or multi-walled carbon nanotubes (MWCNTs). Unfortunately, most data reported in the literature are not recorded in an experimental set-up allowing for the exact quantification of kinetic currents like in an RDE configuration, 4,8,[17][18][19]38 so that the kinetic data at 0.8 V RHE were obtained by the subtracting large capacitive currents under Ar or N 2 from only slightly larger overall currents under oxygen (see above discussion under Comparative ORR Activity Assessment). A first observation from Table I is that the reported mass-specific activities at 0.8 V RHE vary by three orders of magnitude, ranging from 0.04-40•10 −2 A/g Catalyst , which may be compared to 4.0 ± 0.6•10 −2 A/g Catalyst , for our ZrOPc/KB 1000 PO catalyst (see last row; activity averaged over three independent experiments).…”
Section: Literature Comparison Of the Orr Activity Of Zro 2 Basedmentioning
confidence: 99%
“…Zirconium (IV) tetra-tert-butyl-dichlorophthalocyanine (ZrCl 2 Pc(t-Bu) 4 ) was synthesized as reported by Tomachynski et al, 14 using 4-tert-butylphthalonitrile (≥98%, from TCI), ZrCl 4 (≥99.5%), 2-methylnaphthalene (β, 97%), 2-bromonaphthalene (97%), and chloroform (≥99.9%). Iron(II) tetra-tert-butyl-phthalocyanine (FePc(t-Bu) 4 ) was synthesized similarly to Tomoda et al, 15 starting from FeCl 2 (98%), 1,8-diazabicyclo [5.4.0]-5-undec-7-ene (≥99.0%), 2-ethoxyethanol (99%), and chloroform (≥99.9%). The only modification in the original procedures was the replacement of 1,2-dicyanobenzene with 4-tert-butylphthalonitrile as starting precursor, to produce soluble phthalocyanines.…”
Section: Methodsmentioning
confidence: 99%
“…ZrCl 2 Pc(t-Bu) 4 and/or FePc(t-Bu) 4 were deposited on graphitized Ketjenblack (KB graph ) (EA-type from Tanaka Kikinzoku Kogyo K.K.) as described previously, 17 targeting a loading of 12 wt% ZrO 2 /KB graph .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation